Does Early Child Language Predict Internalizing Symptoms in Adolescence? An Investigation in Two Birth Cohorts Born 30 Years Apart. Issue 5 (2nd July 2021) - Thornton, Emma; Patalay, Praveetha; Matthews, Danielle; Bannard, Colin
Abstract : Language is vital for social interaction, leading some to suggest early linguistic ability paves the way for good adolescent mental health. The relation between age‐5 vocabulary and adolescent internalizing symptoms was examined in two U.K. birth cohorts that are nationally representative in terms of sex, ethnicity, and socioeconomic status: the 1970 British Cohort Study (BCS; N = 11, 640) and the Millennium Cohort Study (MCS born 2001; N = 14, 754). In the BCS, no relation between receptive vocabulary and age‐16 self‐reported symptoms was observed (β = 0.00 [−0.03; 0.03]). In the MCS, better expressive vocabulary was associated with more age‐14 self‐reported symptoms (β = 0.05 [0.02; 0.07]). The direction of this effect was reversed for parent‐reported symptoms. All effect sizes were small. The relation between childhood vocabulary and internalizing symptoms varies by generation and reporter.